-2x+9=-2(x-9)+17

Simple and best practice solution for -2x+9=-2(x-9)+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+9=-2(x-9)+17 equation:



-2x+9=-2(x-9)+17
We move all terms to the left:
-2x+9-(-2(x-9)+17)=0
We calculate terms in parentheses: -(-2(x-9)+17), so:
-2(x-9)+17
We multiply parentheses
-2x+18+17
We add all the numbers together, and all the variables
-2x+35
Back to the equation:
-(-2x+35)
We get rid of parentheses
-2x+2x-35+9=0
We add all the numbers together, and all the variables
-26!=0
There is no solution for this equation

See similar equations:

| 7m^2-6=19m | | r15-r5=12 | | 8.5x=5.1 | | -2x-13=4x-13+x | | 2(2x-4)=41-3x | | 1.5-x=-4.5 | | 9=-5x-19/6 | | 2x+2=1(x-1) | | 3a(5)= | | 11x+13x+6=180 | | -2,4(0,5x-0,1)=3(1+0,6x) | | X^3+2x^2-4x-8.5=0 | | (x-20)=(4x-5) | | 80/x=7 | | 3x+17x-6=4(5x+9) | | -2x-13=4x-13+ | | 2=1x-x | | 5c-4+c-3= | | 2(3x-1)+2(4x+5)=106 | | 12n+6=180 | | 3(x+3)=4x+4 | | 12 1+x=3+1 | | 600/x=10 | | (x+14)+108+42=180 | | s-24/5=17 | | 25x-18=7x | | 3p=-12-p | | 2x+18=23-x | | C=2.5n+20 | | 4n3/2=2916 | | x/7=3/17 | | 3.5x=12.5 |

Equations solver categories